2021
DOI: 10.1155/2021/5173035
|View full text |Cite
|
Sign up to set email alerts
|

DCA Protects against Oxidation Injury Attributed to Cerebral Ischemia‐Reperfusion by Regulating Glycolysis through PDK2‐PDH‐Nrf2 Axis

Abstract: Cerebral ischemic stroke (IS) is still a difficult problem to be solved; energy metabolism failure is one of the main factors causing mitochondrion dysfunction and oxidation stress damage within the pathogenesis of cerebral ischemia, which produces considerable reactive oxygen species (ROS) and opens the blood-brain barrier. Dichloroacetic acid (DCA) can inhibit pyruvate dehydrogenase kinase (PDK). Moreover, DCA has been indicated with the capability of increasing mitochondrial pyruvate uptake and promoting ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…Cai et al reported that enhanced glycolysis aggravate cerebral I/R injury after 24-hour reperfusion via the YY1/lncRNA GAS5 complex axis [ 11 ]. Another study also suggested that there is a significant increase in glycolysis in ischemic brain tissue at 24 h of reperfusion, and dichloroacetic acid could produce neuroprotection by regulating poststroke glycolysis via inhibiting PDK2 and activating PDH [ 40 ]. Our present results showed that cerebral I/R-induced glycolysis was significantly inhibited by celastrol at 24 h after reperfusion, which was evidenced by lower glucose consumption, less lactate accumulation, more ATP production, and downregulations of glycolysis-related key enzymes including LDHA, HK2, and Glut1.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al reported that enhanced glycolysis aggravate cerebral I/R injury after 24-hour reperfusion via the YY1/lncRNA GAS5 complex axis [ 11 ]. Another study also suggested that there is a significant increase in glycolysis in ischemic brain tissue at 24 h of reperfusion, and dichloroacetic acid could produce neuroprotection by regulating poststroke glycolysis via inhibiting PDK2 and activating PDH [ 40 ]. Our present results showed that cerebral I/R-induced glycolysis was significantly inhibited by celastrol at 24 h after reperfusion, which was evidenced by lower glucose consumption, less lactate accumulation, more ATP production, and downregulations of glycolysis-related key enzymes including LDHA, HK2, and Glut1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we demonstrated that LPS upregulated ROS generation through PDK2 inhibition even in the next three generations HGFs. It was reported that PDK2 activation has beneficial effects on ROS suppression [ 39 ]. Thus, we reasoned that LPS might mediate irreversible high ROS generation by downregulation of PDK2 expression [ 6 , 40 ], leading to sustained increased mtDNA release activity even in the next-generation HGFs without LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis is significant for neuronal metabolism in cerebral ischemia ( 72 ). Glucose enters brain parenchyma via glucose transporters, which was partially converted to lactate in astrocytes and OLs to meet the energetic demand of neurons ( 62 , 67 ).…”
Section: Mct1 Protects Brain From I/r Injury Via R...mentioning
confidence: 99%